Value of computed tomography derived extra cellular volume fraction in prediction of the pathologic grade of rectal adenocarcinoma - Mary Roman Boles; Karim Atwa; Mohamed Elshal; Rasha Mostafa Mohamed Ali (Egyptian Journal of Radiology and Nuclear Medicine, 2026)
Abstract Background Rectal cancer is one of the leading causes of cancer-related deaths worldwide. The degree of tumor differentiation is one of the most important factors on which the prognosis of rectal cancer. The pathological grading of rectal adenocarcinoma is the gold standard for diagnosis but it is an invasive procedure. Consequently, the aim of the current study was to assess the possibility of prediction of the pathologic grading of rectal adenocarcinoma, using non-invasive CT-derived extracellular volume fraction (ECV). Methods We assessed 30 patients, pathologically diagnosed with rectal adenocarcinoma, all of whom underwent preoperative enhanced CT imaging. CT values were recorded across the plain, venous, and delayed phases and absolute contrast-enhanced differences were calculated. The extracellular volume (ECV) of the primary tumor was determined by assessing CT values in the regions of interest during the plain and delayed phases. Based on the World Health Organization’s 2010, patients were classified into two groups: a low-grade group and a high-grade group. Statistical analyses were performed to compare parameter differences between the groups, and a receiver operating characteristic (ROC) curve was used to evaluate the diagnostic performance. Results Our 30 patients were classified into [17 (56.7%) of low-grade and 13 (43.3%) of high-grade rectal adenocarcinoma]. Their average age was 45.47 years. The ECV was significantly different between the high-grade versus low-grade groups ( P < 0.002), being positively correlated with the pathologic grade. The ROC curve showed ECV had the best efficacy in classifying the pathologic grade of rectal cancer. The area under the curve (AUC) was 0.819. Sensitivity, Specificity, PPV, NPV and Accuracy were 61.5%, 88.2%, 80%, 75% and 76.7% respectively (95% confidence interval: 0.663–0.975). Conclusions CT-derived ECV is a promising noninvasive biomarker for rectal adenocarcinoma. Our findings reinforce the positive correlation between ECV and tumor grade, consistent with previous studies. Standardization of imaging protocols and further validation through large-scale studies will be critical to translate these findings into clinical practice.